Hearing loss is associated with hippocampal atrophy and high cortisol/dehydroepiandrosterone sulphate ratio in older adults. (1st April 2021) - Aoki, Mitsuhiro; Okuda, Hiroshi; Ishihara, Hiromasa; Hayashi, Hisamitsu; Ohashi, Toshimitsu; Nishihori, Takesumi; Kuze, Bunya
Abstract: Objectives: Hearing loss (HL) has been recognised as a prodromal symptom of cognitive disorder with aging. It is still uncertain if HL leads to cognitive impairment directly or through an indirect mechanism. Design: Participants of this study underwent an auditory test, blood tests, and brain MRI. The atrophy rate of the hippocampus (HP) was calculated using voxel-based specific areas. A partial correlation analysis whilst controlling for the effect of age was performed to analyse the factors affecting hearing levels and HP atrophy rate (HP%). Study sample: Thirty-six older adults with hearing impairment Results: The group of participants with moderate or severe HL ( n = 22) had higher cortisol/dehydroepiandrosterone sulphate (C/D) ratio, geriatric depression score (GDS) and HP% than the mild HL or normal hearing group ( n = 14, p < 0.05). The HP% showed a significant positive correlation with the C/D ratio, GDS and the hearing level of high frequency (HF) ( p < 0.05). The C/D ratio was positively correlated with the HP% and the hearing level of the HF ( p < 0.05). Conclusions: Our results suggest that the HL is associated with the atrophy of HP and high C/D ratios in older adults; however, HL may not be causally related to hippocampal atrophy.